2002
DOI: 10.1097/00004836-200202000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Acute Pancreatitis

Abstract: The assessment of the severity of acute pancreatitis (AP) is a critical early step in its management, as severity of AP predicts prognosis. A range of options are available for assessment of severity in AP, including clinical evaluation, standardized prognostic criteria, computed tomography (CT), and biochemical markers. Clinical assessment has limited accuracy for predicting severity early in the course of AP. Therefore, additional assessment using biochemical and radiologic criteria in combination with stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
15

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 59 publications
2
85
0
15
Order By: Relevance
“…In general, the severity of acute pancreatitis is considered to be predictive of the prognosis of the disease according to some specific criteria, such as Ranson's, Glasgow's, the APACHE system and Balthazar's, which differentiate the mild and moderate forms from the severe form (4,6,7) , which were beyond the scope of this study. Our aim was to evaluate the association of necrotizing and edematous types of acute pancreatitis using serum magnesium levels in patients with and without hypocalcemia.…”
Section: Dıscussıonmentioning
confidence: 99%
“…In general, the severity of acute pancreatitis is considered to be predictive of the prognosis of the disease according to some specific criteria, such as Ranson's, Glasgow's, the APACHE system and Balthazar's, which differentiate the mild and moderate forms from the severe form (4,6,7) , which were beyond the scope of this study. Our aim was to evaluate the association of necrotizing and edematous types of acute pancreatitis using serum magnesium levels in patients with and without hypocalcemia.…”
Section: Dıscussıonmentioning
confidence: 99%
“…Recent trial has shown that, C-reactive protein levels > 150 by 48 hours is shown to have positive predictive value for prediction of severity ranging between 37% -77%, which is similar to APACHE II [12]. Serum CRP an acute phase reactant, peaks about third day after initiation of pain.…”
Section: Markers Of Inflammation and Cytokinesmentioning
confidence: 80%
“…Routine laboratory data A recent multicentric trial has reported significant correlation of serum creatinine > 2 mg/dl and blood sugar > 250 mg/dl measured at admission with mortality. Similarly abnormalities in chest radiographs combined with raised serum creatinine > 2mg/dl have been correlated with higher risk [12].…”
Section: Multi-factorial Scoring Systemsmentioning
confidence: 94%
“…In approximately 20% to 25% of patients, however, it is severe and associated with organ failure and significant morbidity and mortality. 38,39 Determining the severity of acute pancreatitis is critical, as patients at high-risk for severe disease require closer monitoring and possible intervention. Several validated scoring systems are available that aim to predict the severity of acute pancreatitis including Ranson's criteria, the Imrie scoring system, the Acute Physiology and Chronic Health Evaluation (APACHE II) scale, and the CT Severity Index (CTSI) ( Table 2).…”
Section: Prognosismentioning
confidence: 99%